Planning and implementation of a countrywide campaign to deliver over 16 million long-lasting insecticidal nets in Mozambique - Jorge A. H. Arroz (Malaria Journal, 2018)
Abstract Background In 2016/2017, Mozambique conducted a countrywide long-lasting insecticidal nets (LLINs) universal coverage campaign (UCC). This paper aims to describe the planning and implementation process of the campaign in Mozambique. Methods A cross-sectional and descriptive design was used for reporting the planning and implementation process of the UCC. The UCC used a collaborative approach, involving institutional and non-institutional actors, namely: National Malaria Control Programme (NMCP), provincial and district health authorities, community members and civil society partners. A new household registration strategy based on coupons, stickers, and one LLIN per two persons as allocation criterion was implemented. The campaign was implemented in phases, allowing for continuous improvement of implementation quality by applying lessons learnt from each phase. Results A total of 7,049,894 households were registered corresponding to a total of 31,972,626 registered persons. A total of 16,557,818 LLINs were distributed between November 2016 and December 2017, corresponding to 97% of LLINs needs based on household registration, and covering 95% of the registered households (6,708,585 households), resulting in an estimated 85% of the total Mozambican population with LLIN access. Conclusions The collaborative planning process and strong coordination of campaign actors allowed Mozambique’s NMCP and partners to successfully carry out the first countrywide LLINs UCC in the country. The increased access to LLINs in households will likely result in increased LLIN use and a reduction of the malaria burden in the country, therefore contributing to the achievement of the 2016–2030 Global Technical Strategy for Malaria goals.